Ultra-flexible composite metamaterials with enhanced and tunable microwave absorption performance. (1st December 2019) - Huang, Lingxi; Duan, Yuping; Yang, Xuan; Gao, Shaohua; Zeng, Yuansong; Ma, Guojia; Zhang, Weiping
Abstract: The microwave absorbers developed so far encounter a bottleneck for the constraint of absorption by deep sub-wavelength thickness. In this work, we report enhanced and tunable structural composite metamaterials, which were fabricated by parallel and orthogonal arrayed Fe-Si alloy ribbons sandwiched between two layers of carbonyl iron powder/polyurethane matrix. It demonstrated a minimum resonance peak value −66.90 dB under deep sub-wavelength thickness (1.25 mm), an extraordinary result that indicated almost complete absorption. The absorption of 90% (reflection loss (RL) < −10 dB) bandwidth covered 10.2 to 18 GHz, almost the entire band of test. The absorbing mechanisms were explored by the simulation models that verified the coupling in the ribbons and the matrix. The composite metamaterials have adaptability during various bending, curling and impact conditions, and the radar-infrared compatible stealth property could also be reached. These results demonstrated that the composite metastructure provides new possibilities for the manufacture of high-performance microwave absorbing materials.